LAWS AND PRINCIPLES OF SOCIO-ECONOMIC THEMATIC MAPMAKING ON BASE OF LOGISTICS MAPS DEVELOPMENT - Гаман, Наталія (Human Geography Journal, 2014)
The important role of logistics processes inUkraineand its integration withEuropeis demonstrated. The role of cartographic providing of process of logistics management is described. The problem of developing of unique logistic map forUkraineis investigated. Different approaches to socio-economic classification of thematic maps are described and specific place of logistic maps in these classifications is defined. The principles of creating thematic maps for special purposes are highlighted. The methods of map development are described. The necessity and importance of development of specialized logistic maps is proved. Their basic content for different types of transportation is given.